2017
DOI: 10.18869/acadpub.jafm.73.242.26983
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation in Guide Vane Opening Process of a Pump-Turbine in Pump Mode

Abstract: During the process of switching conditions in pump-turbine, unstable flow would take place and seriously impact on the stability and safety. This paper deals with the guide vanes' moving process in pump mode through unsteady numerical simulations. Dynamic mesh methodology is used for simulations in which GVO (Guide Vane Opening) from 9mm to 26mm. Simulation results approve that, there are many complex vortex structures and flow blockages phenomena under small GVO condition. Through the mathematical method of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Su et al 28 used STFT to analyze the pressure pulsation signals in different components of the pump turbine. Han et al 29 used STFT to analyze the pressure pulsation signal in the process of guide vane movement of the pump turbine in pump mode. It was found that the main pressure pulsation frequency came from the blade passing frequency and its harmonic frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al 28 used STFT to analyze the pressure pulsation signals in different components of the pump turbine. Han et al 29 used STFT to analyze the pressure pulsation signal in the process of guide vane movement of the pump turbine in pump mode. It was found that the main pressure pulsation frequency came from the blade passing frequency and its harmonic frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex core region also reached the maximum area and number at a moment during the start-up process. Han et al [25] numerically studied the transient characteristics of pump turbines under pumping conditions with different guide vane openings based on the dynamic mesh technology. Compared with the constant guide vane opening condition, the flow in the pump was more unstable under moving guide vane conditions, and there were complex vortex structures and flow blocking phenomena with small guide vane openings.…”
Section: Introductionmentioning
confidence: 99%
“…At present, numerical simulation technology has been widely used in the prediction of turbine pressure fluctuations (Iovănel et al 2019). Dynamic mesh methodology was used for simulations in which GVO (Guide Vane Opening) of a pumpturbine from 9mm to 26mm by Han et al (2017). Yan et al (2010) investigated the influence of water compressibility on pressure fluctuations induced by rotor-stator interaction (RSI) in hydraulic machinery, using the commercial CFD solver ANSYS-CFX.…”
Section: Introductionmentioning
confidence: 99%